Smartphone Addiction and Conflict: An Incentive-Sensitisation Perspective of Addiction for Information Systems. Issue 4 (4th July 2021) - Kuem, Jungwon; Ray, Soumya; Hsu, Pei-Fang; Khansa, Lara
ABSTRACT: This study seeks to develop and test a theory-driven model of technology addiction within the context of smartphone use. Drawing on incentive-sensitisation theory, we proposed a nomological network that centres on a second-order factor of smartphone addiction from a psychological perspective. We empirically evaluated the proposed model against longitudinal data collected from 441 smartphone users. Our analysis from structural equation modelling indicates that our two-factor measurement of smartphone addiction (heightened desire and mobile social interaction) is a parsimonious alternative to the four-factor model. In addition, our findings suggest that addiction and its negative consequences differ in their effects on subsequent perceptions, such as perceived usefulness and perceived enjoyment. We also found that personal innovativeness in information technology and a perception of loneliness explain a large amount of variation in smartphone addiction. Overall, the present study significantly contributes to the information systems literature by offering a refined model of smartphone addiction that effectively describes pathological smartphone use while correcting critical biases in existing models.